El Sistema Penitenciario Ecuatoriano: su ineficacia y vulneración de derechos fundamentales de las personas privadas de libertad por la falta de control institucional. - Carmona Palma, José Ronaldo (2023)
The present Curricular Integration work entitled "The Ecuadorian penitentiary system: its inefficiency and violation of fundamental rights of persons deprived of liberty due to the lack of institutional control" is based on the development that, currently, the Ecuadorian penitentiary system is not fulfilling its established purpose in the legal framework. Therefore, it is essential to analyze the penitentiary system regarding its inefficiency and violation of fundamental rights that occur due to the lack of institutional control in our country, a crisis that the country has been going through in recent years. The penitentiary system in our country is supported, first of all, by our Constitution of the Republic of Ecuador and is in line with the Integral Penal Organic Code, establishing its purpose, which is the fulfillment of a process of comprehensive rehabilitation, the development of capabilities to exercise their rights, fulfill their responsibilities upon regaining their freedom, and the social and economic reintegration of the person deprived of liberty. In this sense, a system is guaranteed in which true social rehabilitation can be given in accordance with human dignity, enabling the effective exercise of rights and responsibilities. Within the development of the research, a thorough study was carried out regarding the factors that produce inefficiency, institutional weakening, and lack of institutional control within our penitentiary system, containing conceptual and legal references from our Constitution of the Republic of Ecuador, Integral Penal Organic Code, and Regulation of the National System of Social Rehabilitation, concluding with comparative law. In the research work, conclusions were developed based on an analytical and legal study of the investigative field, and recommendations were established, concluding with the proposal to generate some alternatives that can be applied to the penitentiary system to strengthen the system and strictly comply with the purpose of the National System of Social Rehabilitation.